Optimal viscous dampers gains for structures subjected to earthquakes. Issue 3 (17th August 2015) - Halperin, Ido; Ribakov, Yuri; Agranovich, Grigoriy
Summary: Passive control is a known method for vibrations damping in civil structures. The simplicity and reliability of passive damping devices makes them a worthy candidate in many practical applications. However, despite of its practical simplicity, the optimal design of passive controller is quite a hard computational problem. In this work, an enhanced optimal viscous passive dampers design method is proposed for seismically excited structures. The optimization is carried out with relation to performance index that consists of an H 2 norm of the system and a quadratic gains norm. An algorithm is suggested for the look after a candidate optimum. It is based on Newton's optimization method with recently developed effective calculation method for the Hessian matrix. Numerical evaluation of the suggested method demonstrates a very fast convergence rate of the design algorithm and proves a performance effective dampers distribution. Copyright © 2015 John Wiley & Sons, Ltd.